Multiple linear regression analysis on factors affecting spending habits among FSKM UiTM Shah Alam undergraduate students / Nur Azmira Mahadi ... [et al.] - Mahadi, Nur Azmira; Mohd Zulkifli, Nur Shuhada; Mat Rani, Ruzanita; Abu Bakar, Syamimi (Unit Penerbitan, UiTM Kelantan, 2022)
Spending habits are a common habit in everyone's life. Students need to spend wisely to manage their finances well. If not, they may experience financial problems. Therefore, this study focused on identifying the factors that affect spending habits among undergraduate students in the Faculty of Computer and Mathematical Sciences (FSKM), Universiti Teknologi MARA (UiTM) Shah Alam campus. This study involved 351 students as the total observations. The research design used in this study was cross-sectional analysis. This study gathered primary data by using questionnaire methods based on research requirements. The data was collected from the questionnaire to obtain opinions from the students. Additionally, the independent variables involved were financial literacy, people's surroundings, and attitudes, while the dependent variable was spending habits. The objective of this study was to investigate the significant effect between the factors (financial literacy, people's surroundings, and attitude) on spending habits among undergraduate students in the FSKM, UiTM Shah Alam campus. The results of this study indicate that there is a significant effect between the factors (financial literacy and people's surroundings) on spending habits among undergraduate students in the FSKM, UiTM Shah Alam. In conclusion, this study is significant for the FSKM undergraduate students to improve their knowledge, and they can take the step to spend wisely when they know the factors affecting their spending habits. Other than that, students will be more aware and cautious of their spending habits in daily life.